Diet and Life Style Modification be able to Reduce the Risk of Coronary Heart Diseases - Nessa, A; Uddin, MM; Ferdousi, S; Hussain, MA (Journal of Bangladesh Society of Physiologist, 2008)
J Bangladesh Soc Physiol. 2006 Dec;(1):40-41.